THE CHARACTER AND ADVENTURES OF A TEENAGE HERO IN GAFUR GHULAM'S WORK "SHUM BOLA" - Kasimova Yulduz Malikovna (Innovate Conferences, 2025)
The article analyzes the artistic interpretation of the image of Karavoy, a teenage hero depicted in the story "Shum Bola" by Gafur Ghulam, one of the outstanding representatives of Uzbek literature. The work explores the character, inner world, attitude to life and the process of growing up of a teenager through various adventures. The hero's life is full of fun, and each of his adventures reveals life lessons, moral standards and educational ideas. The article also theoretically substantiates the role of the work "Shum Bola" in children's and adolescent literature, as well as its significance in the education of the younger generation.
Keywords: Gafur Ghulam, Shum Bola, image of a teenager, Karavoy, character, adventure, children's literature, educational idea, artistic interpretation, psychological development, Uzbek literature.